The Impact of the Dimensions of Employee Empowerment on the Quality of Health Services: A Field Study on the Employees of Taknes General Hospital (Al-Mukhtar Journal of Economic Sciences, 2021)
This study aimed to find out the impact of the dimensions of employee empowerment on the quality of health services. The study population may consist of all the employees in the administrative and medical professions at Taknes General Hospital, whose number is (190) employees. To achieve the objectives of the study, the descriptive and analytical approach was used in processing the data obtained by distributing a questionnaire form to a random sample of (127) employee. The study found that the level of employees 'practice of the hospital's empowerment dimensions was low, and that the level of availability of quality hospital services was low. The study also concluded that there is a positive, statistically significant impact of the employees' empowerment dimensions on the quality of hospital health services. The study recommended the necessity of working to support and strengthen the dimensions of empowerment of hospital staff to improve the quality of health services.
Keywords: Dimensions of Empowering Employees; Quality of Health Services; Hospital